Ultrasonographic findings of gonarthritis caused by toothpick: A case report. Issue 6 (3rd December 2013) - Tang, Yuanjiao; Zhu, Meng; Qiu, Li
ABSTRACT We report a rare case of a 5‐year‐old patient with a toothpick in the knee joint resulting in septic arthritis. The toothpick was detected in the joint by sonography and was confirmed at surgery. A wooden foreign body is an uncommon cause of arthritis. This case report is followed by a discussion of the value of sonography in the diagnosis of wooden foreign‐body arthritis. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound42:379–381, 2014